2016
DOI: 10.3389/fphar.2016.00191
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Properties of the Naturally Occurring Aphrodisiacs: Icariin and Its Derivatives

Abstract: Epimedium (family Berberidaceae), commonly known as Horny Goat Weed or Yin Yang Huo, is commonly used as a tonic, aphrodisiac, anti-rheumatic and anti-cancer agent in traditional herbal formulations in Asian countries such as China, Japan, and Korea. The major bioactive compounds present within this plant include icariin, icaritin and icariside II. Although it is best known for its aphrodisiac properties, scientific and pharmacological studies suggest it possesses broad therapeutic capabilities, especially for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 112 publications
2
86
0
Order By: Relevance
“…Recently, the anti-tumor activity of ICA was reviewed [12]. It exhibited appreciable cytotoxicity against several types of cancer cells [13,14]. ICA demonstrates apoptotic effect via the intrinsic pathway [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the anti-tumor activity of ICA was reviewed [12]. It exhibited appreciable cytotoxicity against several types of cancer cells [13,14]. ICA demonstrates apoptotic effect via the intrinsic pathway [15].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, chemotherapeutic agents used in cancer treatment are able to slow down the progress of the disease; however, they are also toxic toward healthy, non-neoplastic cells (Tan et al, 2016b). An alternative approach currently being explored intensively is pursuing anticancer agents from natural food products to inhibit the onset of cancer (Chung et al, 2010; Chan et al, 2012; Goh et al, 2014; Tan et al, 2016a).…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…Icariin, a bioactive compound extracted from Epimedium , has anti‐cancer, anti‐inflammatory, reproductive, osteoprotective, cardioprotective, immunoprotective, and neuroprotective properties (Tan et al, ). A previous study has reported that icariin can promote osteoblast differentiation and mineralization via regulation of Runx2 and BMP2 (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%